The Influence of Product Quality of Bsi Mobile, Service Quality in the Islamic Perspective, and Customer Understanding on Customer Satisfaction (Study on Students of the Faculty of Economics and Business at Malikussaleh University) - Dahlia, Dahlia; Hafizh, Muhammad (Universitas Ibn Khaldun Bogor, 2024)
This research aims to see the influence of BSI Mobile product quality, service quality from an Islamic perspective and customer understanding on customer satisfaction (Study of students at the Faculty of Economics and Business, Malikussaleh University). The data used in this research is primary data from 97 respondents. The method used to analyze the relationship between variables is multiple linear regression analysis with the Statistical Package for the Social Sciences (SPSS) software. The results of the research show that partially the quality of BSI Mobile products has a positive and significant effect on Customer Satisfaction among Students at the Faculty of Economics and Business, Malikussaleh University, Service quality has a positive and significant effect on Customer Satisfaction among Students at the Faculty of Economics and Business, Malikussaleh University, Understanding has a positive and significant effect on Customer Satisfaction among Students at the Faculty of Economics and Business, Malikussaleh University. Simultaneously, BSI Mobile product quality, service quality and customer understanding have a positive and significant effect on Customer Satisfaction among Students at the Faculty of Economics and Business, Malikussaleh University.